Short-term Effects of Listening to Music on Breathing and Emotional Affect in People Suffering From Chronic Lung Diseases. (January 2022) - Frischen, Ulrike; Bullack, Antje; Roden, Ingo; Kreutz, Gunter
Chronic lung diseases (CLD) are often associated with abnormal, ineffective breathing patterns. Some studies already suggest that nonpharmacological interventions can have positive effects on symptoms related to CLD. However, in the current state of research there is a lack of studies investigating the influence of music listening on breathing rate and oxygen saturation in people affected by CLD. In the present study, we conducted two quasi-experiments to investigate the immediate effects of attentive music listening and music listening combined with a breathing instruction on breathing rate, oxygen saturation, and emotional affect in people affected by CLD and healthy controls. In total, we recruited 58 participants affected by CLD and healthy controls. Participants with CLD and healthy controls were either quasi-randomized to a music-oriented instruction (Experiment 1) or to a breathing-related instruction (Experiment 2). In both experiments we measured physiological measures and emotional affect during a baseline measurement (silence) and during one "relaxing" and one "activating" piece of music. We conducted 3 × 2 repeated measures analyses of variances with condition (baseline/relaxing music/activating music) on the first and group (with/without CLD) on the second factor for both experiments. The results of the experiments suggest that there is no immediate effect of music listening on breathing related outcomes irrespective of the instruction of participants. Moreover, we found some indication that the disease severity might influence the processing of the music. Future studies could investigate whether music listening as a long-term intervention can lead to more promising results in relation to improved breathing.